Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1007/s10236-005-0030-5
|View full text |Cite
|
Sign up to set email alerts
|

Dense water generation on a shelf: the case of the Adriatic Sea

Abstract: The paper overviews recent and past studies of preconditioning, generation and spreading of North Adriatic Dense Water (NAdDW), by analysing both transient episodes and climatological data. The importance of wind stress, heat and water fluxes, and particularly river discharges during the preconditioning and generative period is emphasized, as well as the advection of saline levantine intermediate water from the southeast. After the generation, NAdDW affects deep and bottom layers of the middle and south Adriat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
103
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 129 publications
(105 citation statements)
references
References 61 publications
1
103
0
1
Order By: Relevance
“…During spring and 62 summer it moves downslope along the western Adriatic shelf, strongly hits and fills up deep 63 layers of the Jabuka Pit . Its less dense component goes over the 64 Palagruža Sill (Vilibi and Supi , 2005;Wang et el., 2007) and sinks rapidly towards the 65 bottom of the South Adriatic Pit through the mixing and channelling processes in the Bari 66…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…During spring and 62 summer it moves downslope along the western Adriatic shelf, strongly hits and fills up deep 63 layers of the Jabuka Pit . Its less dense component goes over the 64 Palagruža Sill (Vilibi and Supi , 2005;Wang et el., 2007) and sinks rapidly towards the 65 bottom of the South Adriatic Pit through the mixing and channelling processes in the Bari 66…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Gačić et al (2010) suggested a generalised concept of circulation fluctuations of the central Mediterranean, hypothesizing that the Ionian upper circulation variability is driven by internal dynamics. Namely, formation of dense waters in the Adriatic Sea, the North Adriatic Dense Water (NAdDW, Vilibić and Supić, 2005) and the Adriatic Deep Water (ADW, Vilibić and Orlić, 2001) and its spreading to the deep Ionian Sea influence vorticity balance there, causes a shrinking of the water column along the western perimeter, changes geostrophic balance between the perimeter and the inner Ionian, and induces anticyclonic circulation. The anticyclonic circulation drags a branch of the modified Atlantic water (MAW) towards the Adriatic.…”
Section: Introductionmentioning
confidence: 99%
“…Since the north Adriatic is a shallow sea lying entirely on the continental shelf (average depth 35 m) and is exposed to the winter cold-wind outbreaks, it is a site where shelf dense water occurs, driven by enhanced surface buoyancy loss and cold river runoff. The resulting water mass is named the north Adriatic Dense Water (NAdDW) (Zore-Armanda, 1963;Beg Paklar et al, 2001;Vilibić, 2003;Vilibić et al, 2004;Vilibić and Supić, 2005). This water is cascading towards the deep South Adriatic Pit, through the dynamics which is widely recognized to contribute to the deep water mass changes (Ivanov et al, 2004).…”
Section: Introductionmentioning
confidence: 99%